Study of the Toxic Manifestation of Etoposide the Concomitant Exposure of Acetyl Salicylic Acid As a Protector on the Example of C57Bl/6J Mice Line - O. N. Antosyuk; A. V. Gorskaya; D. V. Petrovskii; T. D. Dubatolova (Антибиотики и Химиотерапия, 2023)
The paper presents the results of evaluating the genetic and cytogenetic toxicity of etoposide, as well as the evaluation results of protective properties of aspirin against the toxicity of etoposide in C57Bl/6J mice. The cytogenetic activity and protective properties assessment was carried out using the chromosome aberration analysis in metaphase cells. Etoposide was tested at a concentration of 15 and 3 mg/kg and aspirin — at a concentration of 25 mg/kg of the animal. The results of metaphase analysis showed that etoposide exhibits cytogenetic toxicity in both doses, and aspirin exhibits protective properties against the toxicity of etoposide at a concentration of 15 mg/kg. The results of chromosome analysis regarding the protective properties of aspirin against etoposide at a concentration of 3 mg/kg are ambiguous and require further experiments.